Solder alloy, solder paste, and solder joint
By optimizing the alloy composition of Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloy, it meets the specific element content ratio relationship, and solves the problem that existing alloys are difficult to meet the tensile strength, shear strength and fall impact resistance after high-temperature placement, and achieves efficient wetting and melting temperature optimization.
Patent Information
- Application Number
- CN202380059026.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-08-11
- Publication Date
- 2025-03-21
AI Technical Summary
The existing Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloys are difficult to meet the tensile strength, shear strength and fall impact resistance after high temperature placement at the same time, and there are insufficient optimization of wetting and melting temperature.
By optimizing the alloy composition of the solder alloy, it is specifically Ag: 0.1 to 3.9%, Cu: 0.1 to 1.0%, Bi: 0.6 to 1.4%, Sb: 5.1 to 7.9%, Ni: 0.01 to 0.30%, Co: 0.001 to 0.100%. The balance consists of Sn, and the specific element content ratio relationship is satisfied, so as to improve the melting temperature, wettability, tensile strength and shear strength of the alloy.
The high tensile strength and shear strength of solder alloy under high temperature conditions are achieved, the wetting and drop impact resistance are improved, and the joint interface failure in high-speed shear test is avoided.
Smart Images

Figure CN119677613A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to solder alloys, solder pastes and solder joints. Background Art
[0002] In recent years, automobiles have been seeking to improve functionality and performance by electrifying mechanical parts. In order to achieve the high functionality and performance of automobiles, it is necessary to deal with miniaturized / high-density electronic equipment mounting technology. In order to cope with this mounting technology, high reliability of the solder joint connecting the printed circuit board and the electronic components is required.
[0003] For example, printed circuit boards mounted near engines are required to be used for a long time under large temperature differences. Hybrid vehicles are equipped with converters that process large amounts of power, and solder joints that can withstand the drive temperature of the converters are required. As such, in automotive electronic equipment mounting technology, high reliability of the solder alloy constituting the solder joints is required, and various studies have been conducted.
[0004] Patent Document 1 discloses a solder alloy suitable for solder pastes requiring high reliability at high use temperatures or operating temperatures of 150° C. or higher. The solder alloy described in the same document is a Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloy having a liquidus temperature of 220° C. or higher.
[0005] Patent Document 2 discloses a Sn-Ag-Cu-Ni-Sb-Bi-Co-P solder alloy containing P to improve creep resistance. In the examples of the same document, solder alloys having a liquidus temperature of 250° C. or less are studied.
[0006] Patent Document 3 discloses a solder alloy that can withstand standing at 150° C. for 480 hours. In the examples of the same document, a Sn—Ag—Cu—Ni—Sb—Bi—Co—In solder alloy containing In is studied.
[0007] Patent Document 4 discloses a solder alloy that exhibits a high melting point and can be operated for a long time at, for example, 150°C or higher in the fields of automobiles, high-power electronic equipment, energy, and LED lighting. For example, a Sn-Ag-Cu-Ni-Bi-Sb-Co-Ge solder alloy having a melting temperature of 220°C or higher is disclosed.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 6730999
[0011] Patent Document 2: Japanese Patent No. 6836040
[0012] Patent Document 3: China Patent Application Publication No. 112475664
[0013] Patent Document 4: International Publication No. 2021 / 043437 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] In Patent Documents 1 to 4, in order to achieve the purpose of the invention described in each document, Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloys with a liquidus temperature of more than 200°C are disclosed. For example, in SiC semiconductor devices, there are high-temperature workers that can achieve more than 200°C. If the melting point of the solder alloy is lower than 200°C, the solder alloy will melt during operation, and thus cannot cope with high-performance electronic components. It is believed that the solder alloys described in Patent Documents 1 to 4 can also cope with the connection of electronic components working at high temperatures as described above. However, as a solder joint, there is a case where other characteristics are poor even if heat resistance is met.
[0016] Although wettability is not evaluated in the invention described in Patent Document 1, paragraph 0043 of the same document states that Bi improves wettability by reducing the surface tension of molten solder. Therefore, in the invention described in Patent Document 1, it is appropriate to contain a large amount of Bi in order to improve wettability.
[0017] On the other hand, the invention described in Patent Document 1 evaluated the tensile strength after high-temperature placement. Moreover, the same paragraph above states: "Although the strength of the alloy is increased by adding Bi, its ductility is significantly reduced, making the solder joint brittle and reducing the thermal fatigue resistance. In the embodiment of the present disclosure, it is preferred to add 1.5 wt% or less Bi in electronic equipment applications in harsh environments." That is, it is recorded that the Bi content is preferably low in electronic equipment applications in harsh environments. Therefore, in the invention described in Patent Document 1, it is appropriate to reduce the Bi content. In view of the above, for the above-mentioned Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloy disclosed in Patent Document 1, the Bi content is reduced in order to improve the tensile strength after high-temperature placement, so the wettability is deteriorated.
[0018] The invention described in Patent Document 2 discloses a Sn-Ag-Cu-Ni-Sb-Bi-Co-P solder alloy containing P. Patent Document 2 is an excellent invention containing P in order to improve creep resistance. However, the invention described in Patent Document 2 is mainly used for preforms. There is a concern that solder powder formed from a solder alloy containing P will aggregate, so it is rarely used as a solder paste. In addition, when a large amount of P is contained, the liquidus temperature will rise.
[0019] Patent Document 2 discloses a solder alloy containing no P in Comparative Example 12. However, although Comparative Example 12 of Patent Document 2 is a Sn-Ag-Cu-Ni-Sb-Bi-Co solder alloy having the same constituent elements as Patent Document 1, the Bi content is small, and therefore wettability is poor.
[0020] The invention described in Patent Document 3 evaluates wettability, tensile strength, heat cycle resistance, and heat resistance. However, in the invention described in Patent Document 3, the characteristics required for the solder joint for connecting the vehicle-mounted electronic component and the substrate are not evaluated. For example, in order to adapt to the environment of being subjected to external stress when driving on a steep road, shear strength and drop impact resistance are required. These are necessary effects for the solder joint. Therefore, in the invention described in Patent Document 3, there is still sufficient room for research on improving shear strength and drop impact resistance.
[0021] In the invention described in Patent Document 4, wettability, hardness, tensile strength, creep characteristics, and cracks at the bonding interface are evaluated. However, shear strength and drop impact resistance are not evaluated, as in Patent Document 3. Therefore, in the invention described in Patent Document 4, as in the invention described in Patent Document 3, there is still ample room for research on improving shear strength and drop impact resistance.
[0022] As mentioned above, the existing Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloy does not satisfy all the above effects at the same time even if it is the same constituent element. This is because no specific effect has been targeted for research in previous studies. In recent years, with the electrification of automobiles, the number of vehicle-mounted substrates has increased, and therefore, it is desired to satisfy a solder alloy that satisfies various effects at the same time.
[0023] An object of the present invention is to provide a solder alloy, a solder paste, and a solder joint which exhibit a moderate melting temperature, excellent wettability, high tensile strength and shear strength, and excellent drop impact resistance.
[0024] Solutions for solving problems
[0025] The present inventors extracted the alloy compositions disclosed in Patent Documents 1 to 4 as solder alloys showing an appropriate melting temperature and investigated the respective problems.
[0026] Patent Document 1 No. 2 discloses a solder alloy of Sn-3.54Ag-1.04Cu-0.05Ni-3.46Sb-0.29Bi-0.05Co (numerical values represent mass %, and the same applies to the following). Patent Document 1 discloses that the liquidus temperature of the solder alloy is 226°C, which is a moderate temperature. However, as mentioned above, it can be seen that the solder alloy has a low Bi content and poor wettability.
[0027] The tensile strength of the above-mentioned solder alloy is poor. It is speculated that this is due to the low content of Bi, so the solid solution strengthening and precipitation strengthening are insufficient, and the low content of Sb, so the solid solution strengthening based on Sb is also insufficient. In addition, the shear strength is also poor. It is speculated that this is due to the high content of Cu, and the coarse intermetallic compound is precipitated at the bonding interface.
[0028] Comparative Example 12 of Patent Document 2 discloses a solder alloy of Sn-3.4Ag-0.70Cu-0.06Ni-6.0Sb-0.5Bi-0.008Co. It is found that this solder alloy, like the solder alloy disclosed in Patent Document 1, has poor wettability due to a small Bi content.
[0029] Example 7 of Patent Document 3 discloses a solder alloy of Sn-3Ag-0.5Cu-0.05Ni-3.5Sb-7Bi-0.03Co-0.2In. Example 38 of Patent Document 4 discloses a solder alloy of Sn-3.5Ag-0.7Cu-0.05Ni-4Sb-3.1Bi-0.05Co-0.01Ge. It is believed that these solder alloys have poor drop impact resistance. It is speculated that this is because the Bi content is high, so Bi segregates and becomes brittle.
[0030] As mentioned above, the Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloys studied in the past are difficult to adapt to the actual situation considering the use environment because they focus on specific effects. However, it is believed that even if the constituent elements are the same as in the past, there is a solder alloy that exhibits a moderate melting temperature, excellent wettability, high tensile strength and shear strength, and further excellent drop impact resistance in one alloy composition.
[0031] Here, for drop impact resistance, since the test substrate itself is dropped, the result includes all factors such as the strength of the substrate, the bonding strength between the wiring and the substrate, etc. Therefore, the destructive factor in drop impact resistance is not limited to the solder alloy.
[0032] Therefore, the inventors of the present invention focused on evaluating the shear strength under conditions that are different from the drop impact resistance and more severe than the drop impact resistance, and conducted a shear strength test at a much higher speed than before. This evaluation is significantly different from the shear strength test conditions conducted in the past, and is an evaluation that can confirm the failure mode when the brazed joint is instantly broken.
[0033] The inventors of the present invention have explored a solder alloy that can simultaneously exert all of the above-mentioned effects in existing solder alloys, and have conducted a detailed study on all the constituent elements again. As a result, the following insights have been obtained: in the Sn-Ag-Cu-Ni-Bi-Sb-Co solder alloy, for the first time, the effects of the content of each constituent element that has not been proven to have an effect in the past have been exerted to a degree that is not problematic in practical use. In detail, the following insights have been obtained and the present invention has been completed: by considering the alloy structure of the solder alloy from melting to solidification, an alloy composition is provided, thereby showing a moderate melting temperature, excellent wettability, high shear strength and tensile strength, and excellent drop impact resistance. In addition, in a high-speed shear test that causes the solder joint to break instantly under conditions more severe than drop impact resistance, an appropriate failure mode is shown.
[0034] The present invention obtained based on the above findings is as follows.
[0035] (0) A solder alloy comprising, in mass%, 0.1 to 3.9% Ag, 0.1 to 1.0% Cu, 0.6 to 1.4% Bi, 5.1 to 7.9% Sb, 0.01 to 0.30% Ni, 0.001 to 0.100% Co, and the balance Sn.
[0036] (1) A solder alloy characterized by having the following alloy composition: in mass %, Ag: 0.1-3.9%, Cu: 0.1-1.0%, Bi: 0.6-1.4%, Sb: 5.1-7.9%, Ni: 0.01-0.30%, Co: 0.001-0.100%, and the balance being Sn.
[0037] (2) The solder alloy according to (0) or (1) above, wherein the alloy composition further contains at least one of In, Ga, As, Fe, Pd, Mn, Zn, Zr and Mg in an amount of 0.1% or less in total by mass%.
[0038] (3) The solder alloy according to any one of (0) to (2) above, wherein the alloy composition contains at least one of the following formulas (1) to (4).
[0039] 426≤(Ag×Cu) / (Ni×Co)≤8530 (1)
[0040] 0.10≤Bi / Sb≤0.28 (2)
[0041] 10.8≤Sn / Sb≤18.0 (3)
[0042] 0.00004≤Bi×Sb×Ni×Co≤0.00254 (4)
[0043] In the above formulas (1) to (4), Sn, Ag, Cu, Bi, Sb, Ni and Co are the contents expressed in mass % of the solder alloy.
[0044] (4) A solder paste comprising the solder alloy according to any one of (0) to (3) above.
[0045] (5) A solder joint comprising the solder alloy described in any one of (0) to (3) above. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is an optical microscope photograph of the PCB substrate surface after the HSS shear test in Example 5.
[0047] Figure 2 This is an optical microscope photograph of the PCB substrate surface after the HSS shear test of Comparative Example 8. DETAILED DESCRIPTION
[0048] The present invention will be described in more detail below. In the present specification, "%" in relation to the composition of the solder alloy means "mass %" unless otherwise specified.
[0049] 1. Solder alloy
[0050] (1) Ag: 0.1~3.9%
[0051] Ag improves the wettability of molten solder and suppresses the increase in melting point. Furthermore, in a high speed shear test (hereinafter referred to as "HSS"), Ag prevents the fracture of the bonding interface and the decrease in drop impact resistance.
[0052] When the content of Ag is less than 0.1%, the wettability of the molten solder deteriorates. The lower limit of the content of Ag is 0.1% or more, preferably 0.5% or more, more preferably 1.0% or more, more preferably 1.4% or more, further preferably 2.0% or more, further more preferably 3.3% or more, and particularly preferably 3.4% or more.
[0053] On the other hand, if the Ag content exceeds 3.9%, coarse Ag3Sn compounds will be formed, causing the bonding interface to be damaged by HSS. In addition, the drop impact resistance will also deteriorate. The upper limit of the Ag content is 3.9% or less, preferably 3.7% or less, and more preferably 3.5% or less.
[0054] (2) Cu: 0.1-1.0%
[0055] Cu improves the wettability of molten solder. In addition, Cu contributes to the increase of tensile strength through precipitation strengthening of solder alloy. Furthermore, it can suppress the damage of the bonding interface caused by HSS. In addition, the shear strength is also improved.
[0056] When the Cu content is less than 0.1%, wettability decreases. The lower limit of the Cu content is 0.1% or more, preferably 0.3% or more, more preferably 0.5% or more, and further preferably 0.6% or more.
[0057] On the other hand, if the Cu content exceeds 1.0%, wettability deteriorates. In addition, coarse Cu6Sn5 compounds crystallized as primary crystals precipitate in the bulk, and thus the tensile strength deteriorates significantly. Furthermore, Cu6Sn5 intermetallic compounds and Cu3Sn intermetallic compounds grow coarsely at the bonding interface, thereby deteriorating the shear strength. In addition, the bonding interface may be damaged due to HSS. The upper limit of the Cu content is 1.0% or less, preferably 0.9% or less, more preferably 0.8% or less, and further preferably 0.7% or less.
[0058] (3) Bi: 0.6-1.4%
[0059] Bi improves wettability. In addition, by making the Bi content appropriate, brittleness is avoided, and thus, damage to the bonding interface due to HSS can be suppressed.
[0060] If the Bi content is less than 0.5%, wettability decreases. The lower limit of the Bi content is 0.6% or more, preferably 0.7% or more, more preferably 0.8% or more, and further preferably 0.9% or more.
[0061] On the other hand, if the Bi content exceeds 1.4%, the steel becomes brittle, and thus, the bonding interface is broken by HSS. The upper limit of the Bi content is 1.4% or less, preferably 1.3% or less, more preferably 1.2% or less, further preferably 1.1% or less, and particularly preferably 1.0% or less.
[0062] (4) Sb: 5.1-7.9%
[0063] Sb is a solid solution strengthening element that intrudes into the Sn matrix, and the part exceeding the solid solubility limit of Sn forms fine SnSb intermetallic compounds, forming a precipitation dispersion strengthening type solder alloy. Therefore, the tensile strength is improved. In addition, compared with Bi, it is not easy to become brittle, so the joint interface damage caused by HSS can be suppressed. In addition, the reduction of drop impact resistance is prevented.
[0064] If the Sb content is less than 5.1%, the precipitation of the SnSb compound becomes insufficient and the tensile strength decreases. The lower limit of the Sb content is 5.1% or more, more preferably 5.3% or more, further preferably 5.5% or more, particularly preferably 5.7% or more, and most preferably 6.0% or more.
[0065] On the other hand, if the Sb content exceeds 7.9%, wettability and drop impact resistance are also reduced. In addition, the bonding interface damage caused by HSS occurs. The upper limit of the Sb content is 7.9% or less, more preferably 7.5% or less, further preferably 7.0% or less, particularly preferably 6.5% or less, and most preferably 6.3% or less.
[0066] (5) Ni: 0.01-0.30%
[0067] The SnNi compound generated by the reaction of Ni and Sn will be dispersed and precipitated in the solder alloy, and the structure of the solder alloy becomes fine, thereby adjusting the tensile strength. In addition, the drop impact resistance and shear strength are improved, and the joint interface damage caused by HSS is suppressed. Furthermore, Ni is uniformly dispersed in the intermetallic compound precipitated near the joint interface between the electrode and the solder alloy, and the intermetallic compound layer is modified, which suppresses the fracture at the joint interface between the electrode and the solder alloy, thereby improving the shear strength.
[0068] If the Ni content is less than 0.01%, the intermetallic compound layer is not modified, the bonding interface is damaged by HSS, and the drop impact resistance is also deteriorated. The lower limit of the Ni content is 0.01% or more, preferably 0.02% or more, more preferably 0.03% or more, further preferably 0.04% or more, particularly preferably 0.05% or more, and most preferably 0.06% or more.
[0069] On the other hand, if the Ni content exceeds 0.30%, the liquidus temperature rises and the wettability deteriorates. In addition, the tensile strength is greatly deteriorated due to the coarse SnNi compound crystallized as the primary crystal. Furthermore, the intermetallic compound grows coarsely at the bonding interface, so the shear strength deteriorates and the bonding interface is damaged due to HSS. The upper limit of the Ni content is 0.30% or less, preferably 0.25% or less, more preferably 0.20% or less, further preferably 0.15% or less, particularly preferably 0.10% or less, and most preferably 0.08% or less.
[0070] (6) Co: 0.001~0.100%
[0071] Co is added together with Ni to enhance the aforementioned effect of Ni. In addition, the SnCo compound generated by its reaction with Sn is dispersed and precipitated in the solder alloy, making the structure of the solder alloy finer. Therefore, the intermetallic compound formed at the bonding interface also becomes finer, improving the shear strength.
[0072] If the Co content is less than 0.001%, the synergistic effect with Ni cannot be exerted, and the shear strength is deteriorated. The lower limit of the Co content is 0.001% or more, preferably 0.003% or more, more preferably 0.004% or more, further preferably 0.005% or more, particularly preferably 0.006% or more, and most preferably 0.007% or more.
[0073] On the other hand, if the Co content exceeds 0.100%, wettability deteriorates. The upper limit of the Co content is 0.100% or less, preferably 0.090% or less, more preferably 0.080% or less, further preferably 0.070% or less, particularly preferably 0.060% or less, and most preferably 0.050% or less.
[0074] (7) At least one of In, Ga, As, Fe, Pd, Mn, Zn, Zr and Mg in a total amount of 0.1% or less
[0075] The solder alloy of the present invention may contain at least one of In, Ga, As, Fe, Pd, Mn, Zn, Zr and Mg in an amount of 0.1% or less in total, in addition to the above-mentioned essential elements, to such an extent that the effects of the present invention are not deteriorated. The lower limit is not particularly limited, but may be 0.0001% or more.
[0076] (8) Residue: Sn
[0077] The solder alloy of the present invention has a balance of Sn, and may contain inevitable impurities in addition to the aforementioned elements. The balance of the solder alloy of the present invention may be composed of Sn and inevitable impurities. Even if inevitable impurities are contained, the aforementioned effects are not affected. It should be noted that P is preferably not contained because it causes the solder powder to aggregate. In addition, when a large amount of P is contained, the liquidus temperature rises.
[0078] (9) Melting point
[0079] The liquidus temperature of the solder alloy of the present invention is preferably 210° C. or higher and 251° C. or lower, and the upper limit is more preferably 235° C. or lower. In consideration of the driving temperature of the electronic component, the liquidus temperature is more preferably 218° C. or higher. The solidus temperature only needs to be 210° C. or higher. The solidus temperature is below the liquidus temperature.
[0080] (10) Formulas (1) to (4)
[0081] 426≤(Ag×Cu) / (Ni×Co)≤8530 (1)
[0082] 0.10≤Bi / Sb≤0.28 (2)
[0083] 10.8≤Sn / Sb≤18.0 (3)
[0084] 0.00004≤Bi×Sb×Ni×Co≤0.00254 (4)
[0085] In the above formulas (1) to (4), Sn, Ag, Cu, Bi, Sb, Ni and Co are the contents expressed in mass % of the solder alloy.
[0086] The solder alloy of the present invention preferably satisfies equations (1) to (4). With respect to equation (1), Ag and Cu are precipitation strengthening elements, and Ni and Co are elements that contribute to the formation of fine precipitates at the bonding interface. In the present invention, it is preferred that not only the tensile strength is improved, or not only the shear strength is improved, but their balance is taken into account so that both effects are effective to a degree that there is no problem in practical use. In addition, if the precipitation behavior of the solid phase in the molten solder is taken into account, the wettability is further improved. Furthermore, it is necessary to avoid damage to the bonding interface in HSS. Therefore, by satisfying equation (1), the balance between tensile strength and shear strength is good, the wettability is better, and damage at the bonding interface caused by HSS can be avoided.
[0087] In the calculation of formulas (1) to (4), the numerical values shown in Table 1 as the measured values of the alloy composition are used. In the calculation, in order to confirm that all the values used are composed of the same number of digits (based on the number of digits shown in the lower limit and upper limit of each relational expression), zeros are added to the values shown in the table. For the unshown numbers, for example, when the Ag content is 1.00% as a measured value, the Ag content used in the calculation of formulas (1) to (4) is corrected in a manner including the additional number of digits "0" according to the number of digits in the Co content. In the content of each constituent element in formulas (1) to (4), the decimal is calculated to 3 decimal places. Moreover, among the digits of the upper limit and the lower limit, formula (1) is rounded to 1 decimal place, formula (2) is rounded to 3 decimal places, formula (3) is rounded to 2 decimal places, and formula (4) is rounded to 6 decimal places. This calculation rule is used in this application and must be processed in the same way for all compositions. Therefore, the calculation involving other compositions described in other documents also uses this rule. The content of Sn in the formula (2) does not take into account inevitable impurities, and the content of inevitable impurities is set to 0 mass %. Therefore, only the essential elements and optional elements are considered.
[0088] The lower limit of formula (1) is preferably 426 or more, more preferably 595 or more, further preferably 661 or more, further preferably 1063 or more, particularly preferably 1190 or more, and may be 2975 or more, 3063 or more, 3188 or more, 4375 or more, 4958 or more, 5313 or more, 5950 or more, or 6563 or more. The upper limit of formula (1) is preferably 8530 or less, more preferably 7438 or less.
[0089] Formula (2) is a relational formula representing the balance of the contents of Bi and Sb. Bi and Sb contribute to the precipitation of fine SnSb compounds, and by controlling the precipitation amount of the solid phase component of the molten solder, wettability can be further improved.
[0090] The lower limit of formula (2) is preferably 0.10 or more, more preferably 0.11 or more, further preferably 0.12 or more, further preferably 0.13 or more, particularly preferably 0.14 or more, and most preferably 0.16 or more, and may be 0.17 or more, 0.18 or more, 0.19 or more, or 0.20 or more. The upper limit of formula (2) is preferably 0.28 or less, more preferably 0.27 or less, further preferably 0.26 or less, further preferably 0.25 or less, particularly preferably 0.24 or less, and most preferably 0.24 or less, and may be 0.23 or less, 0.22 or less, or 0.21 or less.
[0091] Formula (3) is a relational expression that takes into account the balance of the contents of Sn and Sb. Specifically, the effect of improving the tensile strength due to the solid solution strengthening of Sn based on Sb and the effect of improving the shear strength due to the dispersion and precipitation of SnSb compounds are well balanced, and therefore, further improvements in tensile strength and shear strength can be achieved by precipitation of fine SnSb.
[0092] The lower limit of formula (3) is preferably 10.8 or more, more preferably 11.0 or more, further preferably 11.1 or more, further preferably 12.5 or more, particularly preferably 12.6 or more, and most preferably 14.7 or more, and may be 14.8 or more, 15.6 or more, 15.7 or more, 16.2 or more, 16.3 or more, 16.9 or more, 17.0 or more, or 17.5 or more. The upper limit of formula (3) is preferably 18.0 or less, more preferably 17.7 or less, and further preferably 17.6 or less.
[0093] Formula (4) is a relational expression that takes into account the content of the element group that contributes to the precipitation of SnSb compounds, SnNi compounds, and SnCo compounds. By well-balanced adjustment of the contents of Bi, Sb, Ni, and Co, excessive hardening of the solder alloy can be suppressed, and the damage to the bonding interface in the HSS can be fully suppressed. In addition, in formula (4), excessive addition of any element will lead to deterioration of wettability, so formula (4) is also a relational expression that contributes to further improvement of wettability.
[0094] The lower limit of formula (4) is preferably 0.00004 or more, more preferably 0.00010 or more, further preferably 0.00020 or more, further preferably 0.00041 or more, particularly preferably 0.00098 or more, and most preferably 0.00102 or more. It can be 0.00106 or more, 0.00109 or more, 0.00115 or more, 0.00131 or more, 0.00134 or more, 0.00136 or more, 0.00141 or more, 0.00146 or more, 0.00152 or more, or 0.00154 or more. The upper limit of formula (4) is preferably 0.00254 or less, more preferably 0.00253 or less, further preferably 0.00246 or less, further preferably 0.0245 or less, particularly preferably 0.00237 or less, and most preferably 0.00230 or less. It can be 0.00228 or less, 0.00224 or less, 0.00219 or less, 0.00211 or less, 0.00204 or less, 0.00196 or less, 0.00192 or less, 0.00182 or less, 0.00176 or less, 0.00170 or less, or 0.00163 or less.
[0095] 2. Solder paste
[0096] The solder paste of the present invention is a mixture of solder powder having the above alloy composition and a flux. The flux used in the present invention is not particularly limited as long as it can be soldered by conventional methods. Therefore, a suitable mixture of commonly used rosin, organic acid, activator, and solvent can be used. There is no particular limitation on the mixing ratio of the metal powder component and the flux component in the present invention, preferably the metal powder component: 70 to 90 mass%, the flux component: 10 to 30 mass%.
[0097] 3. Brazing joints
[0098] The solder joint of the present invention is suitable for connecting an IC chip in a semiconductor package to its substrate (interposer substrate), or connecting a semiconductor package to a printed circuit board. Here, the "solder joint" refers to a joining portion of electrodes.
[0099] 4. Others
[0100] The method for manufacturing the solder alloy of the present invention can be carried out according to conventional methods. Regarding the joining method using the solder alloy of the present invention, for example, the reflow method can be carried out according to conventional methods. In addition, when the solder alloy of the present invention is used for joining, the cooling rate during solidification can be considered to make the structure more refined. For example, the solder joint is cooled at a cooling rate of 2 to 3°C / s or more. Other joining conditions can be appropriately adjusted according to the alloy composition of the solder alloy.
[0101] The solder alloy of the present invention can be produced by using a low α-ray material as its raw material. Such a low α-ray alloy can suppress soft errors when used to form solder bumps around a memory.
[0102] Example
[0103] The following evaluations were performed using solder alloys having the alloy compositions shown in Table 1: Evaluation 1: solidus temperature and liquidus temperature, Evaluation 2: wettability, Evaluation 3: tensile strength, Evaluation 4: shear strength, Evaluation 5: HSS shear strength, Evaluation 6: drop impact resistance. Each evaluation method is described below.
[0104] Evaluation 1. Solidus temperature and liquidus temperature
[0105] For the solder alloys having the alloy composition described in Table 1, the respective temperatures were obtained from the DSC curve. The DSC curve was obtained as follows: using a DSC (model: Q2000) manufactured by Seiko Instruments Inc., the temperature was raised at 5°C / min in the atmosphere. The liquidus temperature was obtained from the obtained DSC curve as the melting temperature. In addition, the solidus temperature was also evaluated from the DSC curve. When the solidus temperature is above 210°C and the liquidus temperature is below 235°C, it is judged as "◎". When the solidus temperature is above 210°C and the liquidus temperature is above 235°C and below 251°C, it is judged as "0". When the solidus temperature is below 210°C or the liquidus temperature exceeds 251°C, it is judged as "×".
[0106] Evaluation 2. Wettability
[0107] (1) Preparation of test panels
[0108] The wettability of the solder alloy was determined by the Meniscograph test method. A flux ("ES-1100" manufactured by Senju Metal Industry Co., Ltd.) was applied to a copper plate (width 10 mm × length 30 mm × thickness 0.3 mm). The copper plate coated with the flux was heated at 120°C in an atmosphere for 15 minutes to obtain a test plate. Five such test plates were prepared for each of the examples and comparative examples shown in Table 1.
[0109] (2) Evaluation method
[0110] The obtained test plates were immersed in solder tanks containing molten solder having the alloy composition shown in Table 1, and the zero crossing time (sec) was obtained. Here, Solder Checker SAT-5100 (manufactured by RHESCA) was used as a test device, and the evaluation was performed in the following manner. The solder wettability was evaluated based on the average value of the zero crossing time (sec) of 5 test plates of each embodiment and each comparative example. The test conditions were set as follows.
[0111] Immersion speed in solder bath: 10mm / sec
[0112] Immersion depth of solder tank: 4mm
[0113] Immersion time in solder bath: 10 sec
[0114] Solder tank temperature: 255°C
[0115] The shorter the average value of the zero crossing time (sec), the faster the wetting speed and the better the solder wettability.
[0116] (3) Criteria for determination
[0117] When the average value of the zero crossing time (sec) is 1.3 seconds or less, it is judged as "◎", when it exceeds 1.3 seconds and is 1.5 seconds or less, it is judged as "○", and when it exceeds 1.5 seconds, it is judged as "×".
[0118] Evaluation 3. Tensile strength
[0119] The tensile strength was measured in accordance with JIS Z3198-2. Each solder alloy listed in Table 1 was poured into a mold to produce a test piece with a measured length of 30 mm and a diameter of 8 mm. The prepared test piece was stretched at room temperature with a stroke of 6 mm / min using Type 5966 manufactured by Instron, and the strength of the test piece when it broke was measured.
[0120] When the tensile strength was 60 MPa or more, it was evaluated as "◎", when it was 55 MPa or more and less than 60 MPa, it was evaluated as "○", and when it was less than 55 MPa, it was evaluated as "×".
[0121] Evaluation 4. Shear strength
[0122] A 3216 chip resistor component with a size of 3.2×1.6×0.55 (mm) was soldered to a solder pattern (1.6×0.8 mm) in a FR-4 glass epoxy substrate with a size of 110 mm×110 mm and a thickness of 1.6 mm. For soldering, a metal mask with a thickness of 150 μm was used, and after printing the solder paste on the substrate, it was heated in a reflow oven with a peak temperature of 245°C and a holding time of 40 seconds. After that, the shear strength was measured using a joint strength tester STR-5100 at a shear speed of 6 mm / min and a test height of 100 μm from the substrate surface.
[0123] When the shear strength was 65 N or more, it was evaluated as "◎", when it was 45 to 64 N, it was evaluated as "○", and when it was less than 45 N, it was evaluated as "×".
[0124] Evaluation 5. HSS shear test
[0125] The HSS shear test was performed as follows. A solder ball with a diameter of 0.3 mm having the alloy composition of Table 1 was placed on a PCB substrate using a glass epoxy resin substrate of FR-4 with a size of 36 mm × 50.4 mm and a thickness of 1.2 mm. Then, the peak temperature was set to 245°C and the holding time was set to 40 seconds, and the heat was applied in a reflow oven. After that, a shear test was performed using a high-speed bonding tester 4000HS at a shear speed of 4000 mm / sec (240000 mm / min), and the failure mode was visually confirmed.
[0126] When the failure mode was block failure, it was evaluated as “◎”, when it was block failure + joint interface failure, it was evaluated as “○”, and when it was joint interface failure, it was evaluated as “×”.
[0127] Evaluation 6. Drop impact resistance
[0128] A Cu-plated CSP with bumps and 196 electrodes of 12×12 mm in size was prepared. Solder paste was applied to the center of a 30×120 mm glass epoxy printed circuit board, the CSP was mounted, and heated in a reflow oven to solder the CSP to the printed circuit board.
[0129] The two ends of the printed circuit board with the CSP soldered are fixed to the drop jig at a distance of 1 cm from the jig. The drop jig is dropped from a height that will load the drop jig with an acceleration of 1500G, and the printed circuit board is impacted. At this time, the center of the printed circuit board with both ends fixed to the jig vibrates, and the solder joint between the printed circuit board and the CSP is impacted by the vibration. In this drop test, the progress of cracks in the solder joint of the CSP is confirmed by whether the resistance value increases by 50% from the initial value.
[0130] When the resistance value increased by 50% from the initial value more than 100 times, it was evaluated as “◎”; when the resistance value increased by 50% from the initial value 50 to 100 times, it was evaluated as “0”; when the resistance value increased by 50% from the initial value less than 50 times, it was evaluated as “×”.
[0131] [Table 1]
[0132]
[0133] [Table 2]
[0134]
[0135] *Underlined elements are outside the scope of the present invention.
[0136] [Table 3]
[0137]
[0138] [Table 4]
[0139]
[0140] As shown in Table 1, in Examples 1 to 58, results that are not problematic in practical use were obtained in all evaluations. Among them, the Examples satisfying the formulas (1) to (4) all received the highest evaluations in the above-mentioned evaluation criteria.
[0141] On the other hand, in Comparative Example 1, the Ag content was small, so the wettability was poor. In Comparative Example 2, the Ag content was large, so the bonding interface was broken in the HSS shear test, and the drop impact resistance was also poor.
[0142] In Comparative Example 3, the Cu content was small, so the wettability was poor. In Comparative Example 4, the Cu content was large, so the wettability, tensile strength and shear strength were poor, and the bonding interface was broken in the HSS shear test.
[0143] In Comparative Example 5, since the Ni content was low, the drop impact resistance was poor and the bonding interface was broken in the HSS shear test. In Comparative Example 6, since the Ni content was too high, all evaluation items were poor.
[0144] In Comparative Example 7, the tensile strength was poor due to the small Sb content, and in Comparative Example 8, the wettability was poor due to the large Sb content, and the bonding interface was broken in the HSS shear test.
[0145] In Comparative Example 9, the Bi content was small, so the wettability was poor. In Comparative Example 10, the Bi content was large, so the bonding interface was broken in the HSS shear test.
[0146] In Comparative Example 11, the shear strength was poor due to the small content of Co. In Comparative Example 12, the wettability was poor due to the large content of Co.
[0147] In Comparative Examples 13 and 14, the Sb content was small and the Bi content was large, so the bonding interface was damaged in the HSS shear test and the drop impact resistance was poor. In Comparative Example 15, the Cu content was large and the Sb and Bi contents were small, so the wettability, tensile strength, and shear strength were poor, and the bonding interface was damaged in the HSS shear test.
[0148] Figure 1 This is an optical microscope photograph of the PCB substrate surface after the HSS shear test of Example 5. Figure 2 This is an optical microscope photograph of the PCB substrate surface after the HSS shear test of Comparative Example 8. Figure 1It is clear that in Example 5, the solder alloy remains on the electrode, and therefore, it is known that the bulk is broken. Figure 2 In the example, no solder alloy remained and the intermetallic compound was exposed, so it was found that the joint interface was broken. It was confirmed that the examples after Example 5 were also bulk failure or bulk failure + joint interface failure.
Claims
1. A solder alloy, characterized in that: The alloy composition includes, by mass%, 0.1 to 3.9% Ag, 0.1 to 1.0% Cu, 0.6 to 1.4% Bi, 5.1 to 7.9% Sb, 0.01 to 0.30% Ni, 0.001 to 0.100% or less Co, and the balance Sn.
2. The solder alloy according to claim 1, wherein The alloy composition further contains at least one of In, Ga, As, Fe, Pd, Mn, Zn, Zr and Mg in an amount of 0.1% or less in total by mass%.
3. The solder alloy according to claim 1 or 2, wherein The alloy composition contains at least one of the following formulas (1) to (4): 426≤(Ag×Cu) / (Ni×Co)≤8530 (1) 0.10≤Bi / Sb≤0.28 (2) 10.8≤Sn / Sb≤18.0 (3) 0.00004≤Bi×Sb×Ni×Co≤0.00254(4) In the above formulas (1) to (4), Sn, Ag, Cu, Bi, Sb, Ni and Co are the contents expressed in mass % of the solder alloy.
4. A solder paste, characterized in that: The solder alloy comprises the solder alloy according to claim 1 or 2.
5. A brazing joint, characterized in that: The solder alloy comprises the solder alloy according to claim 1 or 2.
Citation Information
Patent Citations
High temperature ultra-high reliability alloys
WO2021043437A1
Solder alloy, solder paste, and electronic circuit board
CN104487203A
High Reliability Lead-Free Solder Alloys For Harsh Environment Electronics Applications
CN107635716A
Solder alloy, solder ball, solder preform, solder paste and solder joint
CN111745321A
High Reliability Lead-Free Solder Alloys For Harsh Environment Electronics Applications
CN113146093A